Activity patterns of leopards (Panthera pardus) and temporal overlap with their prey in an arid depredation hotspot of southern Africa. (April 2021) - Puls, Sam; Teichman, Kristine J.; Jansen, Corlé; O'Riain, M. Justin; Cristescu, Bogdan
Abstract: The ecology of wildlife in remote arid regions with free-range livestock farming activities remains largely unexplored. We studied the temporal activity patterns of African leopards ( Panthera pardus ) in relation to prey in Namaqualand, South Africa, a semi-desert ecosystem with extensive livestock farming and a protected area. Camera trapping in winter and summer 2014–2015 ( n = 95 stations) showed that leopards had high temporal overlap with aardvark ( Orycteropus afer ) and lagomorphs, and partial overlap with red hartebeest ( Alcelaphus buselaphus ), the only reintroduced ungulate present in leopard diet ( n = 82 scats). Goats ( Capra hircus ) had the lowest temporal overlap with leopard but comprised most biomass in leopard scat. Sheep ( Ovis aries ) and cattle ( Bos sp. ) also had generally low temporal overlap with leopards, with cattle contributing less biomass to leopard diet than sheep. Leopards were active primarily at night across seasons ( n = 103 photos). These results suggest that leopards hunted at night when prey were resting and presumably less vigilant, or that they effectively predated some species during daylight. We recommend research on leopard hunting behaviour and habitat selection, and broad-scale implementation of livestock management such as guardian dogs, herders, and protective enclosures to minimize livestock-carnivore interactions and facilitate coexistence. Highlights: Free-ranging livestock on arid and semi-arid landscapes are exposed to wild predators. Goats and sheep in Namaqualand, South Africa had low temporal overlap with leopards. However, small livestock especially goats contributed high biomass to leopard diet. Extensive livestock management (i.e. day and night) will likely minimize depredation. Reintroduced red hartebeest overlapped leopard activity but were rarely consumed.